Critical care nurses’ views on medication administration: an organizational perspective - Mansour, Mansour (2009)
The Organizational Safety Space Model (OSSM) was developed as a tool to investigate the factors which influence the safety of industrial operations. It is applied in this study to investigate the safety of medication administration in adult critical care settings, including Intensive Care Units and High Dependency Units. In this study, semi-structured interviews were conducted with 33 adult critical care nurses. The participants’ views on the safety of medication administration were analyzed using OSSM. The data suggested that the safety of medication administration is subject to complex influences of many organizational factors. Socio-cultural factors, including lack of questioning culture, the perceived hierarchy of professions and the nature of nursing education, were identified as influential safety factors. Furthermore, organizational complexity and structures created tension between organizational, ethical and structural priorities on one side, and the requirements of safe management of medication in critical care a setting on the other, inevitably leading to tradeoffs among these organizational priorities. Some organizational factors are difficult to classify according to the OSSM and the model is not fully operational in identifying factors related to the safety of medication administration. While the OSSM’ theoretical framework helped to focus on the underpinning safety factors in the organization of medication administration, it remains unproven as an operational tool to understand the full complexities and interplays between the organization structures, professional differences and socio-cultural impacts on the safety of medication administration in adult critical care setting.